Balik Kampung : a journalism feature. - Chiang, Gracia Yun Jia. (2009)
The Southeast Asian city-state of Singapore ranks as one of the most globalized countries in the world. While the city of 4.6 million citizens is feeding off its open-door policies and has prospered as an economic giant, it finds itself struggling to deal with an increasing global demand for its most precious resource — human talent. It is because of Singapore’s size that this story matters. For a nation that relies heavily on its citizens, talent bleed is a fearful thought. Among the nation’s solutions to counter brain drain: welcome home the overseas Singaporean. This story is a hard look at the country’s shot at getting its overseas citizens back, and how it misses the mark. It is also a tale of the kind of welcome returnees get when they arrive home. Their narratives highlight the obstacles and struggles that Singaporean returnees face in the homecoming journey.